Separation and mapping of multiple genes that control IgE level in Leishmania major infected mice - Badalová, J; Svobodová, M; Havelková, H; Vladimirov, V; Vojtísková, J; Engová, J; Pilcík, T; Volf, P; Demant, P; Lipoldová, M (Genes and immunity, 2002)
The strain BALB/cHeA (BALB/c) is a high producer, and STS/A (STS) a low producer of IgE after Leishmania major infection. We analyzed this strain difference using 20 recombinant congenic (RC) BALB/c-c-STS/Dem (CcS/Dem) strains that carry different random subsets of 12.5% of genes of the strain STS on the BALB/c background. Strains CcS-16 and -20 exhibit a high and a low IgE level, respectively. In their F(2) hybrids with BALB/c we mapped nine Leishmania major response (Lmr) loci. Two of them we previously found to influence IgE level in CcS-5. IgE production in CcS-16 is controlled by loci on chromosomes 2, 10, 16 and 18 and in CcS-20 by loci on chromosomes 1, 3, 4, 5 and 8. The STS alleles of loci on chromosomes 1, 4, 5, 8 and 10 were associated with a low, whereas the STS alleles on chromosomes 16 and 18 with a high IgE production. The loci on chromosomes 2 and 3 have no apparent individual effect, but interact with the loci on chromosomes 10 and 1, respectively. The loci on chromosomes 10 and 18 were mapped in the regions homologous with the human regions containing genes that control total serum IgE and intensity of infection by Schistosoma mansoni, suggesting that some Lmr loci may participate in the pathways influencing atopic reactions and responses to several parasites. The definition of genes controlling anti-parasite responses will permit a better understanding of pathways and genetic diversity underlying the disease phenotypes.
Keywords: imunoglobulin E; Crosses, Genetic; Leishmania major; myši kongenní; Female; leishmanióza kožní; myši inbrední BALB C; zvířata; myši; křížení genetické; Mice; Leishmaniasis, Cutaneous; ženské pohlaví; Male; Chromosome Mapping; mapování chromozomů; Animals; Mice, Congenic; mužské pohlaví; Mice, Inbred BALB C; Immunoglobulin E